Integrated Reporting Practice of Small and Medium size Businesses : Evidence from Bangladesh (International Journal of Scientific Research and Management (IJSRM), 2022)
Companies that only focus on the fundamentals of financial reporting will fall short in today’s competitive and uncertain market climate. Non-financial performance data, which may be used to measure a company’s long-term financial health, is missing from the current financial report. To address the issue, the Integrated Reporting Framework has been developed by IIRC. The aim of the study is to determine to what extent the annual reports of the SMEs reflect the elements of Integrated Reporting. All the SMEs listed on the Dhaka and Chittagong stock exchanges have been considered and their annual reports have been analysed to assess the level of disclosure being made following the Integrated Reporting framework. The findings reveal that SMEs listed on the stock exchanges in Bangladesh are sluggish to embrace IR due to limited resources, culture and leadership, stakeholder demand, regulatory requirements, lack of awareness about IR, and the nature of their business. Thus, SMEs’ annual reports in Bangladesh contain very little information about the elements mentioned by IR. However, Bangladeshi SMEs are likely to benefit greatly in terms of long-term viability and value generation as a result of the holistic concept that IR seeks to build.